2012
DOI: 10.1108/20423891211197712
|View full text |Cite
|
Sign up to set email alerts
|

Can work‐based learning programmes help companies to become learning organisations?

Abstract: Purpose -The idea of the learning organisation as an aspiration for a continuous process of learning has become widely accepted by many organisations. The purpose of this paper is to examine whether demand-led higher education work-based learning programmes can help nurture a supportive culture of learning and continuous improvement that helps companies to become learning organisations. Design/methodology/approach -An analysis of students' work-based negotiated projects was undertaken to determine the extent t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 26 publications
0
12
0
3
Order By: Relevance
“…Social interactions are of vital importance at each level, as information gains significance only when social actors (such as people, groups, organizations, etc.) determine its meaning through social interactions and refer it to their own experiences (Ions and Minton, 2012;Steensma et al, 2012;Tynjala, 2008).…”
Section: Literature Review 21 Learning In Social Interactionsmentioning
confidence: 99%
“…Social interactions are of vital importance at each level, as information gains significance only when social actors (such as people, groups, organizations, etc.) determine its meaning through social interactions and refer it to their own experiences (Ions and Minton, 2012;Steensma et al, 2012;Tynjala, 2008).…”
Section: Literature Review 21 Learning In Social Interactionsmentioning
confidence: 99%
“…Work-based learning programmes co-delivered with employers can be very demanding for higher education staff and institutions (Meakin and Wall, 2013). Ions and Minton (2012) used a case study approach to examine the link between a University work-based learning programme and organisational learning and concluded that "the results suggest that consideration should be given to embedding organisational learning principles into the design of work-based learning programmes at higher education level" (p. 30). Abraham (2012, p. 4) identifies key features of University-level work-based learning and observes that "Work-Based Learning appears to focus on learning in the workplace by individuals or as teams for the purpose of application".…”
mentioning
confidence: 99%
“…De esta forma encontramos argumentos que hablan de la modernización de los empleados (Basit et al 2015;Felce, 2017;Ferrández-Berrueco, 2016a;Marzo et al 2008;Whittington & Ferrández, 2007) y del aprendizaje de nuevos conocimientos y las últimas innovaciones que los empleados pueden adquirir a través de estudiantes en prácticas (Antcliff et al 2016;Geller et al 2016;Guinart, 2005). Esto último implica que además se promueva la incorporación de la cultura del aprendizaje (White, 2012) introduciendo el ciclo de mejora continua (Ions & Minton 2012).…”
Section: Responsabilidad Social Corporativa (Rsc)unclassified
“…Por otra parte, encontramos otros factores relacionados con la reflexión profesional en cuanto que la colaboración permite una mejor aceptación de los cambios y obliga al entendimiento mutuo (White, 2012), haciendo que la empresa se aleje de lo tradicional (Whittington & Ferrández, 2007;Ions & Minton 2012). En resumen, la colaboración transforma a las empresas en organizaciones de aprendizaje (Bolívar, 2007;Ions & Minton, 2012), un concepto que ya introdujo Peter Senge (1992) en el ámbito empresarial y que con posterioridad se ha incorporado al contexto educativo Finalmente, dentro de este apartado hemos incluido los factores relacionados con la evaluación, puesto que la colaboración proporciona a la empresa un referente para evaluar su eficiencia (Hegarty et al 2011) y al mismo tiempo es una forma de evaluar el desempeño de los empleados (Siebert & Costley, 2013) promoviendo así una mejor cualificación de los empleados actuales y futuros (Felce et al 2016).…”
Section: Responsabilidad Social Corporativa (Rsc)unclassified
See 1 more Smart Citation